Ultrastructure and chemical analysis of osmophores in Apocynaceae - Capelli, Natalie do Valle (2018)
Apocynaceae presents the flowers with the highest degree of synorganization among the eudicots and highly elaborated pollination mechanisms associated with the high diversity of glands. The osmophore stands out as responsible to produce a floral scent which attracts pollinators and, despite its fundamental relevance for pollination, its structure and mechanism of production and release of the perfume is essentially unknown in Apocynaceae. This present work aims to characterize morphologically and ultrastructurally the osmophores of Apocynaceae, besides chemically identifying the compounds that constitute the floral scent. Species from two subfamilies were selected to describe the diversity of osmophores and types of scent in the family. The osmophores were firstly located histochemically and, later, this region was processed for transmission electron microscopy. Micromorphological analysis was performed by scanning electron microscopy, and the identification of volatile oils made by GC-MS. Osmophores are located on the adaxial surface of the free portion of the petals. They varied in the shape of epidermal cells, striation of the cuticle and presence of trichomes. This gland is mostly formed by secretory epidermis and parenchyma, except in Plumeria, where the osmophores are exclusively epidermal. The secretory cells presented thick walls in the Asclepiadoideae and secretion produced by plastids and SER in all species. Several vesicles perform the intercellular transport of secretion, as well as its release to the environment. However, Plumeria and Ditassa transfer the secretion produced to the vacuole before releasing it, and Tabernaemontana has a mixed release process. The composition of the scent varied among species, with great production of hydrocarbons, alcohols, ketones or monoterpenes depending on the species. Apocynaceae presents a high morphological and metabolic diversity in the osmophores which cannot be correlated with their morphology, subcellular organization, period of secretion release or pollination syndrome. This is the first comprehensive structural study of osmophores in this family that points out to very distinct evolutionary processes that may be related to multiple emergences in the phylogeny and speciesspecific associations with pollinators